Enhancing Supply Chain Agility Through AI-Driven Robotic Process Automation and SAP Variant Configuration - Ncube, Zanele M. (MZ Journal of Artificial Intelligence, 2024)
This paper explores the role of AI-driven Robotic Process Automation (RPA) and SAP Variant Configuration (VC) in enhancing supply chain agility. In today’s rapidly evolving marketplace, organizations must be able to swiftly adapt to changes in customer demands and operational challenges. RPA automates repetitive, rule-based tasks, increasing efficiency and reducing errors, while SAP VC facilitates the management of product complexity and customization. Together, these technologies enable supply chains to achieve greater flexibility, speed, and responsiveness. The paper discusses the integration of RPA and SAP VC, their benefits, real-world applications, and future trends. By leveraging these innovations, organizations can enhance operational performance, improve customer satisfaction, and gain a competitive edge.